2015
DOI: 10.1016/j.stemcr.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Activin/Nodal Signaling Supports Retinal Progenitor Specification in a Narrow Time Window during Pluripotent Stem Cell Neuralization

Abstract: SummaryRetinal progenitors are initially found in the anterior neural plate region known as the eye field, whereas neighboring areas undertake telencephalic or hypothalamic development. Eye field cells become specified by switching on a network of eye field transcription factors, but the extracellular cues activating this network remain unclear. In this study, we used chemically defined media to induce in vitro differentiation of mouse embryonic stem cells (ESCs) toward eye field fates. Inhibition of Wnt/β-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…Moreover, zebrafish and mice with Nodal mutations display defects in eye development such as cyclopia as well as loss of ath5 ( ATOH7 ) expression , an essential gene for RGC development . Furthermore, recently a role for Nodal/Activin signaling in establishment of the eye field has been described in hESC and mESC differentiation and addition of IDE1, another Nodal agonist molecule similar to IDE2, has been used to enhance stem cell differentiation to RPE . Surprisingly, we noticed that DSM alone decreased RGC differentiation, perhaps due to its weaker activity against Activin/Nodal .…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, zebrafish and mice with Nodal mutations display defects in eye development such as cyclopia as well as loss of ath5 ( ATOH7 ) expression , an essential gene for RGC development . Furthermore, recently a role for Nodal/Activin signaling in establishment of the eye field has been described in hESC and mESC differentiation and addition of IDE1, another Nodal agonist molecule similar to IDE2, has been used to enhance stem cell differentiation to RPE . Surprisingly, we noticed that DSM alone decreased RGC differentiation, perhaps due to its weaker activity against Activin/Nodal .…”
Section: Discussionmentioning
confidence: 77%
“…Our finding that activin A causes similar effects on some, but not all, non-retinal populations suggests that activin alone is insufficient to induce these gene expression changes ( Figure S1 ). Other studies on neuralization and eye field specification in differentiating ESCs have shown that activin signaling coordinates with bFGF, BMP, and Wnt pathways ( Bertacchi et al., 2015 , Lupo et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activin A treatment of differentiating ESCs caused increased expression of eye field and RPC markers ( Bertacchi et al., 2015 ). We investigated the effect of activin signaling on ESC-derived cultures that had reached the RPC stage, a time frame that corresponds to in vivo dates at which expression of activin A and its receptors were detected in the embryonic eye and retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations